Essential oils of Lavandula stoechas subsp. luisieri as antifungal agent against fungi from strawberry tree fruit - Domingues, Joana (2021)
L. stoechas subsp. luisieri is one of the five spontaneous species of the genus Lavandula that occurs spontaneously in Portugal. The chemical profile and antifungal activity of L. stoechas subsp. luisieri essential oils were investigated. The essential oil of two phenological stages was isolated by hydrodistillation and their chemical components analyzed by GC-FID/GC-MS. The minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC) of both essential oils were determinate to verify antifungal activity against different strains of fungi isolated from strawberry tree. The fungi tested were Aspergillus carbonarius, Rhizopus stolonifer, Penicillium brevicompactum, Aureobasidium pullulans and Saccothecium rubi. Essential oils were characterized by a high percentage of oxygenated monoterpenes (46-64%) such as trans-α-necrodyl acetate (12.58%), fenchone (5.97%), 1,8-cineole (4.84%) and 5-methylene-2,3,4,4-tetramethylcyclopenten-2-enone (10.97%) were the major compounds in essential oil from dormancy stage, while the main compounds in flowering stage were trans-α-necrodyl acetate (26.90%), trans-α-necrodol (13.02%), lavandulyl acetate (6.53%) and linalool (5.82%). A strong antifungal activity of the essential oils was found against all strains, with MIC and MFC values ranged from 0.07-0.29 µL/mL and 0.58-9.33 µL/mL, respectively.